1977
DOI: 10.1073/pnas.74.1.248
|View full text |Cite
|
Sign up to set email alerts
|

Transient inhibition of initiation of S-phase associated with dimethyl sulfoxide induction of murine erythroleukemia cells to erythroid differentiation.

Abstract: The murine erythroleukemia cell (MELC) line in suspension culture can be induced to differentiate to erythroid cells by various compounds, including dimethyl sulfoxide (Me2SO). Analysis of the cell cycle, during differentiation induced by Me2SO, using thymidine incorporation, thymidine labeling index, and relative DNA content per cell as measured by flow microfluorometry, demonstrates a transient inhibition of entry of (2), accumulation of globin mRNAs (3-6), a and f globin synthesis (7), increase in heme s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
0

Year Published

1978
1978
1996
1996

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(58 citation statements)
references
References 19 publications
2
56
0
Order By: Relevance
“…An early manifestation of termination of cell division in MELC appears to be a transient prolongation of the GI phase of the cell cycle, which can be detected after cell transit through one complete S phase in the presence of inducer (8)(9)(10). After up to 4-5 terminal cell divisions, induced MELC are arrested in a GI-like phase of the cell cycle.…”
mentioning
confidence: 99%
“…An early manifestation of termination of cell division in MELC appears to be a transient prolongation of the GI phase of the cell cycle, which can be detected after cell transit through one complete S phase in the presence of inducer (8)(9)(10). After up to 4-5 terminal cell divisions, induced MELC are arrested in a GI-like phase of the cell cycle.…”
mentioning
confidence: 99%
“…c-K-ras, a 600-bp StuI-EcoRI fragment from the mouse c-K-ras first exon (18) DNA synthesis and growth curves. DNA synthesis was measured as described previously (46) Run-on transcription assays. Transcription was measured by performing run-on transcription assays (27).…”
Section: Methodsmentioning
confidence: 99%
“…MEL cells respond to induction with DMSO by undergoing a temporary withdrawal from the cell cycle (46). This transitory decrease in DNA synthesis occurs roughly during the time of suppression of c-myc expression.…”
Section: Mouse Erythroleukemia (Mel) Cells (Also Known Asmentioning
confidence: 99%
See 1 more Smart Citation
“…HC treatment in the absence of dimethy( sulfoxide doubled the production of virus. Alterations in DNA metabolism (1,2) and structure (3) are among the many changes that occur in Friend leukemia (FL) cells undergoing dimethyl sulfoxide (Me2SO)-induced erythrodifferentiation (4). The increase in single-stranded breaks in DNA, detected early after Me2SO treatment (5,6), before globin mRNA appeared (Scher, unpublished), suggested that these breaks might play a role in differentiation in this system as postulated in lens differentiation (7,8) and in transcription (9,10).…”
mentioning
confidence: 99%